Kabin berasap / Muhammad Ilhan Harith Muhammad Faizul ...[et al.] - Muhammad Faizul, Muhammad Ilhan Harith; Nasrullah, Ahmad Adham Irfan; Zainal, Muhammad Iskandar Shah; Md Fauzi, Muhammad Haziq; Arman, Farez Azra’e; Mohd Yusri, Muhammad Amir Haziq (2023)
Kabin Berasap is the name of the business, which sells western foods from a variety of menus. Fresh ingredients are used in western cuisine to meet consumer demand. This business sells western cuisine, including items from the main menu like chicken and lamb chops, fish and chips, and beef steak. The business name is Kabin Berasap. It is a partnership business located in Bandar Dato' Onn, Tebing. The business operates in the food and beverage sector. The idea behind the business is "Kabin Berasap." We call the concept container we're using for the food truck a "kabin" theme. "Berasap" because we want to draw customers in with its appealing aroma and smoke. This business is situated in Tebing, Bandar Dato Onn, a popular tourist destination. People who work nearby and are between the ages of 6 and 65 make up the business's target market. We also believe that our commitment and effort will help us achieve our goal of becoming the most well-known food truck in Malaysia by providing the highest-quality western foods at affordable prices. For more people to enjoy the best Western cuisine Malaysia has to offer, Kabin Berasap must continue. The business plan makes it clear that Kabin Berasap can help a lot of customers, especially in terms of great food. Our neighbourhood customers can visit us easily and have a wonderful dining experience at Tebing, Bandar Dato Onn because there are many parking spaces close by. We can effectively prepare and provide customers with the best Western cuisine by opening Kabin Berasap.